A Flow Cytometry-Based Approach for the Isolation and Characterization of Neural Stem Cell Primary Cilia - Monaco, Sara; Baur, Katja; Hellwig, Andrea; Hölzl-Wenig, Gabriele; Mandl, Claudia; Ciccolini, Francesca (Frontiers in Cellular Neuroscience, 2019)
In the adult mammalian brain the apical surface of the subependymal zone (SEZ) is covered by many motile ependymal cilia and a few primary cilia originating from rare intermingled neural stem cells (NSCs). In NSCs the primary cilia are key for the transduction of essential extracellular signals such as Sonic hedgehog (SHH) and platelet-derived growth factor (PDGF). Despite their importance, the analysis of NSC primary cilia is greatly hampered by the fact that they are overwhelmingly outnumbered by the motile cilia. We here take advantage of flow cytometry to purify the two cilia types and allow their molecular characterization. Primary cilia were identified based on immunoreactivity to the marker adenylate cyclase type III (AC3) and differential levels of prominin-1 whereas motile cilia displayed immunoreactivity only to the latter. Consistent with the morphological differences between the two classes of cilia, enrichment of motile but not of primary cilia positively correlated with size. Moreover, we observed age-dependent variations in the abundance of the two groups of ciliary organelles reflecting the changes associated with their development. The two cilia groups also differed with respect to the expression of signaling molecules, since PDGF receptor (PDGFR) α, smoothened (Smo) and CXC chemokine receptor (CXCR) 4 were only detected in isolated primary but not motile cilia. Thus, our novel method of cilia isolation and characterization by flow cytometry has the potential to be extended to the study of cilia from different tissues and organs, providing a powerful tool for the investigation of primary cilia in physiological and pathological conditions.